The Immature Gut Barrier and Its Importance in Establishing Immunity in Newborn Mammals - Weström, Björn; Arévalo Sureda, Ester; Pierzynowska, Kateryna; Pierzynowski, Stefan G.; Pérez-Cano, Francisco-José (Frontiers in Immunology, 2020)
The gut is an efficient barrier to protect against invasion of pathogenic microorganisms and potential harmful macromolecules, in addition to its primary function of digestion and nutrient absorption. Contrary to the restricted passage in adulthood, an enhanced macromolecular transfer takes place over the immature intestine early in life. This is due to a high endocytic capacity of the intestinal epithelial cells during the foetal and/or neonatal periods. The timing and extent of the transepithelial transfer is dependent on animal species, with a prominent non-selective macromolecular transfer in newborn ungulates, e.g., pigs, during the first days of life, and a selective transfer of mainly immunoglobulin G (IgG) mediated by the FcRn receptor in suckling rodents, e.g., rats and mice. In primates, maternal IgG is transferred already during foetal life over the placenta, while intestinal macromolecular transfer is largely restricted in human neonates, albeit higher than in the adult. This review will focus on the developmental processes in the intestinal epithelium during the perinatal period having effects on the macromolecular passage and the possible impact of such passage on the establishment of immunity in the young. The intestinal macromolecular transfer provides passive immune protection by maternal IgG antibodies from an experienced mother and possibly has beneficial extra-immune effects on organ maturation in the offspring. Moreover, the intestinal transfer during the foetal/neonatal periods results in an increased microbial and food antigen exposure and presentation to the underlying immune system being immature and naïve. This likely affects the maturation of the immune system and shifts the response towards tolerance induction instead of sensitization or inflammation, as usually seen in adulthood. Ingestion of mother’s milk and the dietary transition to complex food at weaning, as well as the transient changes in the gut microbiota during the neonatal period, are also involved in the resulting immune response. Any disturbances in the timing and/or balance of these parallel processes, i.e., intestinal epithelial maturation, mucosal immune maturation and luminal microbial colonization due to, e.g., preterm birth, infection, antibiotic use or nutrient changes during the neonatal period, might affect the outcome of the immune establishment in the infant.